Dietary protein intake is associated with body mass index and weight up to 5 y of age in a prospective cohort of twins. - Pimpin, L; Jebb, S; Johnson, L; Wardle, J; Ambrosini, G (American Society for Nutrition, 2015)
Background Few large epidemiological studies have investigated the role of post-weaning protein intake in excess weight and adiposity of young children, despite children in the UK consistently consuming protein in excess of their physiological requirements. Objectives To investigate whether a higher proportion of protein intake from energy beyond weaning is associated with greater weight gain, higher Body Mass Index (BMI) and risk of overweight or obesity in children up to 5 years of age. Methods Participants were 2154 twins from the GEMINI cohort. Dietary intake was collected using a 3-day diet diary when the children were on average 21 months old. Weight and height were collected every three months, from birth to 5 years. Longitudinal models investigated associations between protein intake and BMI, weight and height, adjusting for age at diet diary, gender, total energy intake, birth weight/length and rate of prior growth and clustering within families. Logistic regression investigated protein intake in relation to the odds of overweight or obesity at 3 and 5 years of age. Results A total of 2154 children had 5.7 (SD 3.2) weight and height measurements up to 5 years. Total energy from protein was associated with higher BMI (β 0.043 (95%CI 0.011;0.075) and weight (β 0.052 (95%CI 0.031;0.074)), but not height (β 0.088 (95%CI - 0.038;0.213), between 21 months and 5 years. Substituting % energy from fat or carbohydrate for % energy from protein was associated with decreases in BMI and weight. Protein intake was associated with a trend in increased odds of overweight or obesity at 3 years (OR 1.10 95% CI 0.99;1.22, p=0.075), but the effect was not significant at 5 years. Conclusions A higher proportion of energy from protein during the complementary feeding stage is associated with greater increases in weight and BMI in early childhood in this large cohort of UK children.